2000
DOI: 10.1097/01241398-200011000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Apolipoprotein E ϵ4 Allele in Cerebral Palsy

Abstract: The apolipoprotein E gene, which is located on chromosome 19, has three alleles (epsilon2, epsilon3, and epsilon4). Several recent publications associate the presence of the apolipoprotein E epsilon4 allele with the occurrence of neurologic diseases, and consider it a risk factor for the development of central nervous system affections. A group of 40 patients with cerebral palsy was studied and compared to a control group of 40 subjects, and higher occurrence of the allele epsilon4 in the group of subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Commercial Applied Biosystems Taqman SNP probes (Foster City, California) were used to genotype single nucleotide polymorphisms (SNPs) using 0.5ng of genomic DNA (Table 1). We genotyped the following SNP’s that have been previously associated with CP: tumor necrosis factor-α (TNF-α) -308 (rs1800629) (8), interleukin-8 (IL-8) -251 (rs4073) (6), lymphotoxin 60 (rs1041981) (6, 11), endothelial nitric oxide synthase (eNOS) -922 (rs1800779) (11), inducible nitric oxide synthase (iNOS) -231 (rs1137933) (6), endothelial protein C receptor (EPCR) 219 (rs867186) (6), mannose binding lectin (MBL) 54 (rs1800450) and 52 (rs5030737) (8), factor V Leiden (FVL) 506 (rs6025) (10), methyltetrahydrofolate reductase (MTHFR) 1298 (rs1801131) and 667 (rs1801133) (10), prothrombin 20210 (rs1799963) (10), platelet activator inhibitor (PAI-1) 11053 (rs7242) (11), and apolipoprotein E (apo E) E2 and E4 alleles (rs429358 and rs7412) (15, 16, 18). The IL-6 -174 polymorphism was previously studied in this population (5), and therefore was not included in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial Applied Biosystems Taqman SNP probes (Foster City, California) were used to genotype single nucleotide polymorphisms (SNPs) using 0.5ng of genomic DNA (Table 1). We genotyped the following SNP’s that have been previously associated with CP: tumor necrosis factor-α (TNF-α) -308 (rs1800629) (8), interleukin-8 (IL-8) -251 (rs4073) (6), lymphotoxin 60 (rs1041981) (6, 11), endothelial nitric oxide synthase (eNOS) -922 (rs1800779) (11), inducible nitric oxide synthase (iNOS) -231 (rs1137933) (6), endothelial protein C receptor (EPCR) 219 (rs867186) (6), mannose binding lectin (MBL) 54 (rs1800450) and 52 (rs5030737) (8), factor V Leiden (FVL) 506 (rs6025) (10), methyltetrahydrofolate reductase (MTHFR) 1298 (rs1801131) and 667 (rs1801133) (10), prothrombin 20210 (rs1799963) (10), platelet activator inhibitor (PAI-1) 11053 (rs7242) (11), and apolipoprotein E (apo E) E2 and E4 alleles (rs429358 and rs7412) (15, 16, 18). The IL-6 -174 polymorphism was previously studied in this population (5), and therefore was not included in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The ε4 allele of the apolipoprotein E (apoE) gene has also been associated with CP in more than one population (15, 16), though not all studies have supported this finding (17, 18). Few genetic studies of CP have been conducted in the US, and the majority of findings have yet to be corroborated in an independent cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reports (24, 25) of subjects with CP have not found the strengths of association found in the two earlier reports of association between CP and APOE genotype (13, 14). Wu et al reported results of association studies between candidate gene SNPs and cerebral palsy from a diverse, general population of 334,333 newborn infants from the Kaiser Permanente Health System, inclusive of healthy and sick infants.…”
Section: Discussionmentioning
confidence: 62%
“…Previous case – control studies of pediatric populations reporting association between APOE genotypes and CP, a common outcome after HIE, did not target assessment of only infants with neonatal hypoxic-ischemic injury (13, 14). Our results demonstrate no association between APOE genotype and moderate or severe disability, or specifically with CP, in this more restrictive injury phenotype, and no modification from use of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation